RETRACTED: Evaluation of all-for-one tourism development level: Evidence from Xinjiang production and construction corps, China - Yingyin Cui; Chunxiang Zhang; Bin Jiang; Ziwei Qin; Zhennan Liu; Yiwan Yang (PLoS ONE, 2025)
All-for-one tourism represents a pivotal strategy to facilitate the transformation and enhancement of the tourism sector and promote the coordinated development of the economy and society within the contemporary context of China. Since its introduction by the Ministry of Culture and Tourism in 2016, governments at all levels have actively promoted the development of all-for-one tourism with remarkable results. Xinjiang Production and Construction Corps (XPCC), a unique governance system in Xinjiang, is rich in natural and cultural tourism resources and has achieved specific results in developing all-for-one tourism. Nevertheless, it also faces the outstanding problems of a low level of development and insufficient motivation. Therefore, this study focused on the XPCC as the research area and established an evaluation index system to assess the level of all-for-one tourism development across three dimensions: tourism potential, tourism benefit, and tourism format. Subsequently, a comprehensive analysis was conducted regarding the development level, spatial distribution characteristics, the coupling and coordination mechanisms among these dimensions, and the classification of tourism destinations. The results show that (1) XPCC’s four major regions have unbalanced all-for-one tourism development, revealing disparities among divisions. (2) Spatial analysis shows that the Tianshan North Slope is advantageous, while southern Xinjiang and border areas are disadvantageous. (3) The coupling degree spans four stages, with significant differences in spatial distribution. (4) Tourism destinations can be categorized into three types: industrial integration-driven, economic and social-driven, and advantageous resource-driven. Accordingly, the optimization development strategies for all-for-one tourism in the XPCC were proposed: (1) integrating resources to optimize supply, (2) enhancing infrastructure to improve services, (3) deepening industrial integration, (4) strengthening brand building, (5) promoting regional cooperation. These strategies provide insights for optimizing all-for-one tourism development in similar regions.